She gets the girl - Lippincott, Rachael; Derrick, Alyson (Simon & Schuster Books for Young Readers, 2022)
Alex Blackwood is really good at getting the girl she wants, but coming from a broken home with an alcoholic mother, she finds commitment difficult - even when she thinks she is in love. Impossibly awkward Molly Parker has a crush on the cool Cora Myers, but she does not know how to even start a conversation, much less make a connection. At college together in Pittsburgh, Alex decides that helping Molly snag Cora will prove to her own flame that she is not totally selfish - but things do not work out as the two have planned.